Self-Reported Prevalence of Gluten-Related Disorders and Adherence to Gluten-Free Diet in Colombian Adult Population (2016)
ABSTRACT: Background. Celiac disease seems to be rare in Colombians, but there are currently no data about the prevalence rates of symptomatic adverse reactions to gluten or adherence to gluten-free diet (GFD) in this population. Aim. to evaluate the self-reported prevalence rates of adverse reactions to gluten, adherence to GFD, and gluten-related disorders at population level in Colombia. Methods. A self-administered questionnaire-based cross-sectional study was conducted in a population from Northwest Colombia. Results. The estimated prevalence rates were (95% CI) 7.9% (6.5-9.6) and 5.3% (4.1-6.7) for adverse and recurrent adverse reactions to wheat/gluten, respectively, adherence to GFD 5.9% (4.7-7.4), wheat allergy 0.74% (0.3-1.4), and nonceliac gluten sensitivity 4.5% (3.5-5.8). There were no self-reported cases of celiac disease. Prevalence of self-reported physician-diagnosis of gluten-related disorders was 0.41% (0.17-0.96). Most respondents reported adherence to GFD without a physician-diagnosis of gluten-related disorders (97.2%). The proportion of gluten avoiders was 17.2% (15.2-19.5). Most of them did not report recurrent adverse reactions to wheat/gluten (87.0%). Conclusions. Nonceliac gluten sensitivity is rarely formally diagnosed in Colombia, but this population has the highest prevalence rate of adherence to GFD reported to date. Consequently, most respondents were avoiding wheat- and/or gluten-based products for reasons other than health-related symptoms.